Practicing oral history with immigrant narrators - McKirdy, Carol 1953- (Practicing oral history series, 2015)
Introduction to oral history -- Working with the immigrant community -- Trauma -- Cultural awareness -- The importance of language -- Using an interpreter in an oral history interview -- Using photographs in immigrant oral history projects -- An oral history project step-by-step -- Savan, a life story case study with an immigrant narrator